Multifaceted changes in water availability with a warmer climate - Binglan Gu; Sha Zhou; Bofu Yu; Kirsten L. Findell; Benjamin R. Lintner (npj Climate and Atmospheric Science)
Abstract Climate warming alters spatial and seasonal patterns of surface water availability (P-E), affecting runoff and terrestrial water storage. However, a comprehensive assessment of these changes across various hydroclimates remains lacking. We develop a multi-model ensemble approach to classify global terrestrial hydroclimate into four distinct regimes based on the mean and seasonality of P-E. P-E is projected to become increasingly variable across space and time. Wet regions with low and high seasonality are likely to experience more concentrated increases in wet-season runoff by up to 20%, highlighting potential increases in flood-related vulnerability. Low-seasonality regions exhibit faster wet-season increases and more rapid dry-season decreases in soil moisture, heightening the likelihood of water scarcity and drought. Conversely, dry regions with high seasonality are less sensitive to climate change. These findings underscore the multifaceted impacts of climate change on global water resources, necessitating the need for tailored adaptation strategies for different hydroclimate regimes.